Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Studio Warnails di Karawang - Januarsisti, Tiara; Isyanto, Puji; Sumarni, Neni (J-MAS (Jurnal Manajemen dan Sains), 2024)
The research conducted at Studio Warnails aimed to determine the impact of digital marketing and service quality on purchasing decisions for products and services. A quantitative method was chosen for this study. Non-probability sampling was conducted through purposive sampling approach. The population in this study consisted of consumers who had purchased products or services from Studio Warnails and followed the Instagram account @warnails.id, with a sample size of 168 participants. Data processing was carried out using SPSS ver.27. The findings of the research indicate that digital marketing and service quality have a positive and significant impact, both partially and simultaneously, on purchasing decisions at Studio Warnails.